Features governing symbiont persistence in the squid-vibrio association - Koch, Eric J. (2013)
Experimental studies of the interaction between host and symbiont in a maturing symbiotic organ have presented a challenge for most animal-bacterial associations. Advances in the rearing of the host squid Euprymna scolopes have enabled us to explore the relationship between a defect in symbiont light production and late-stage development (e.g., symbiont persistence and tissue morphogenesis) by experimental colonization with specific strains of the symbiont Vibrio fischeri. During the first four weeks post-inoculation of juvenile squid, the population of wild-type V. fischeri increased 100-fold; in contrast, a strain defective in light production (Δlux) colonized normally the first day, but exhibited an exponential decline to undetectable levels over subsequent weeks. Co-colonization of organs by both strains affected neither the trajectory of colonization by wild type, nor the decline of Δlux levels. Uninfected animals retained the ability to be colonized for at least two weeks post-hatch. However, once colonized by the wild-type strain for 5 days, a subsequent experimentally induced loss of the symbionts could not be followed by a successful recolonization, indicating the host’s entry into a refractory state. However, animals colonized by the Δlux before the loss of their symbionts were receptive to recolonization. Analyses of animals colonized with either a wild-type or a Δlux strain revealed slight, if any, differences in the developmental regression of the ciliated light-organ tissues that facilitate the colonization process. Thus, some other feature(s) of the Δlux strain’s defect also may be responsible for its inability to persist, and its failure to induce a refractory state in the host.